The Development of Science E-modules in Junior High Schools Integrated with Al-Qur'an Verses and Assisted by Virtual Simulations on the Subject of Vibration, Waves and Sound - Permana, Niki Dian; Ramadan, Cahaya Pitri; Syarif, Muhammad Ilham; Mahartika, Ira; Setyaningsih, Rini; Wibowo, Firmanul Catur (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This research aims to produce junior high school science teaching materials in the form of e-modules that are integrated with verses from Al-Qur'an and assisted by virtual simulations on the subject of vibrations, waves and sound. The research method used is development research (R & D) which is adapted from the Borg and Gall development model. The stages of development research carried out are research and information collecting, planning, developing preliminary product, preliminary field testing, and main product revision. Data collection was carried out using questionnaires given to students, material experts, teaching materials experts, science-Al Qur'an integration experts and science teachers to determine student responses, validity and practicality of the products being developed. The research results showed that the validity score of material experts was 89.25% in the very valid category, science-AlQur'an integration experts were 71% in the valid category, and teaching materials experts were 72.62% in the valid category. So overall the average validity of the products developed is 77.63% in the very valid category. The practicality test results obtained a score of 94.27% in the very practical category and student responses were 97.67% in the very good category. So it can be concluded that the integrated junior high school science e-module with Al-Quran verses assisted by virtual simulations on vibration, wave and sound material that was developed obtained very valid and very practical results and received a very good response from students.Keywords: Teaching Materials, E-Module, Integrated Al-Qur'an Verses, Virtual Simulation, Vibration, Waves and Sound